Preparation of Nanographene-Based Copolymer Nanocomposites: Thermal Decomposition Kinetic, Optical, and Electrical Behaviors - Barim, Esra; Demirelli, Kadir (Springer Heidelberg, 2026)
The poly(4-methacryloyloxyphenyl-4'-methoxystyryl ketone-co-methyl methacrylate) [P(MPMESK0.25-co-MMA)] was synthesized using a free radical copolymerization method at 60 degrees C. The composition of the copolymer was estimated by 1H-NMR. The nanocomposites of P(MPMESK0.25-co-MMA)-loaded 9 and 11 wt% nanographene (NG) were produced using the ultrasonic homogenizer sonicator. The FT-IR, 1H-NMR, GPC, TGA, XRD, and SEM techniques were used to characterize the copolymer and composites. The thermal behavior of P(MPMESK0.25-co-MMA) partially heated up to 270, 310, 340, and 380 degrees C was investigated by FT-IR analysis. A six-membered anhydride ring in the copolymer backbone formed at 340 degrees C and higher temperatures. TG measurements were used to analyze the thermal decomposition processes of pure P(MPMESK0.25-co-MMA) and P(MPMESK0.25-co-MMA)/NG 11 wt% composite. Apparent activation energies for thermal decomposition of P(MPMESK0.25-co-MMA)/NG 11 wt% were determined using the Flynn-Wall-Ozawa (FWO) and Kissinger-Akahira-Sunose (KAS) methods at a temperature range of 200 and 400 degrees C for a weight loss of approximately 70%. The average activation energies determined from the FWO and KAS methods were 86.3 and 80.3 kJ/mol, respectively. The dielectric and electrical behaviors of the P(MPMESK0.25-co-MMA) and P(MPMESK0.25-co-MMA)/NG 11 wt% composite were investigated at room temperature. The dc activation energy for dc conductivity of nanocomposite was calculated as 1.092 eV. Optical properties such as absorption, reflectance, refractive index, absorption edge, direct band gap of the copolymer, and composites were investigated from their optical examinations in the wavelength region of 200-800 nm. It was found that the optical energy gap values had shifted to the lower energies with the doping of NG.
Keywords: Nanographene; Copolymer; Electrical conductivity; Dielectric properties; Optical properties